Anthraquinones as Potential Antibiofilm Agents Against Methicillin-Resistant Staphylococcus aureus - Song, Zhi-Man; Zhang, Jun-Liang; Zhou, Kun; Yue, Lu-Ming; Zhang, Yu; Wang, Chang-Yun; Wang, Kai-Ling; Xu, Ying (Frontiers in Microbiology, 2021)
Biofilms formed by methicillin-resistant Staphylococcus aureus (MRSA) are one of the contributing factors to recurrent nosocomial infection in humans. There is currently no specific treatment targeting on biofilms in clinical trials approved by FDA and antibiotics remain the primary therapeutic strategy. In this study, two anthraquinone compounds isolated from a rare actinobacterial strain Kitasatospora albolonga R62, 3,8-dihydroxy-l-methylanthraquinon-2-carboxylic acid (1) and 3,6,8-trihydroxy-1-methylanthraquinone-2-carboxylic acid (2), together with their ten commercial analogues 3-12 were evaluated for anti-bacterial and anti-biofilm activities against MRSA, which led to the discovery of two potential anti-biofilm anthraquinone compounds anthraquinone-2-carboxlic acid (6) and rhein (12). The structure-activity relationship analysis of these anthraquinones indicated that the hydroxyl group at the C-2 position of the anthraquinone skeleton played an important role in inhibiting biofilm formation at high concentrations, while the carboxyl group at the same C-2 position had a great influence on the anti-bacterial activity and biofilm eradication activity. The results of crystal violet and methyl thiazolyl tetrazolium staining assays, as well as scanning electron microscope and confocal scanning laser microscopy imaging of compounds 6 and 12 treatment groups showed that both compounds could disrupt pre-formed MRSA biofilms possibly by killing or dispersing biofilm cells. RNA-Seq was subsequently used for the preliminary elucidation of the mechanism of biofilm eradication, and the results showed up-regulation of phosphate transport related genes in the overlapping differentially expressed genes of both compounds treatment groups. Herein, we propose that anthraquinone compounds 6 and 12 could be considered as promising candidates for the development of anti-biofilm agents.